Inversion polymorphism, longevity, and body size in a natural population of Drosophila buzzatii. - Rodriguez, C.; Fanara, J.J.; Hasson, E. (Evolution, 1999)
In this study we present the results of an analysis of differential longevity associated with Drosophila buzzatii second chromosome inversion karyotypes based on the assessment of more than 1000 individuals collected in a natural population. Comparisons of inversion frequencies between emerged and bait-collected flies showed not only that inversion arrangements were associated with differential longevity, but also that selection was sex specific. Because each individual fly was scored for thorax length and karyotype, we were able to show that longevity selection favoring larger flies coupled with the average effect of inversions on thorax length can account for the change of inversion frequencies due to longevity in females. The observed genotypic-by-sex interaction could be an important mechanism involved in the maintenance of the polymorphism. Arrangement 2Jz[3] , which was shown to impaired fecundity in two independent previous studies, exhibited a positive effect on longevity. This pattern of negative pleiotropy may be another plausible mechanism accounting for the maintenance of the polymorphism.